Prevalence of vitamin D deficiency in Lalitpur, Nepal - RC, Laxmi; Koirala, Srijana (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Sunlight exposure is the most important source of vitamin D for human beings. We can get vitamin D from other sources such as diet and dietary supplements as well. Human body synthesizes most of the vitamin D from exposure to direct ultraviolet sunlight. The deficiency of vitamin D is a major public health problem worldwide. It is deficiency of vitamin D level when blood serum which is below 30ng/ml. The deficiency is associated with various musculoskeletal diseases and autoimmune diseases. The early detection of deficiency plays an important role to prevent those diseases. The aim of the study is to find the prevalence of vitamin D deficiency. Method: A retrospective study was conducted in Star Hospital Sanepa, Lalitpur, Nepal, from first January 2018 to 31 December 2018. All patients attended outpatient door with multiple complaints like; backache, muscle pain, leg pain was tested for Vit D3. Result: A total of 786 patients had tested vitamin D levels, where 717 (91.2%) had deficiency and 69 had normal levels. Adult females were found to be vitamin D deficient than the adult male population.